An inversion method for polarity distribution of atmospheric water-soluble organic matter. Issue 12 (4th August 2020) - Lee, Wen-Chien; Chen, Jing; Kuwata, Mikinori
Abstract: The polarity distribution of water-soluble organic matter (WSOM) is believed to play an important role in determining the water uptake properties of aerosol particles. The 1-octanol−water partitioning method has been proposed as a method for classifying WSOM by polarity. However, the broad partitioning functions of the method make it difficult to estimate polarity distribution. In this study, a data inversion technique was developed to determine the polarity distributions of WSOM. The inversion technique was evaluated against artificially generated polarity distributions with corresponding uncertainties. In addition, the technique was combined with positive matrix factorization (PMF) analysis of the aerosol mass spectrometric data, allowing an estimation of the polarity distribution of the PMF factors. The technique was applied to WSOM generated by smoldering mosquito coils. As the 1-octanol−water partitioning coefficients of WSOM correlate well with water solubility, future application of this method to the investigation of hygroscopic growth and cloud condensation nucleus (CCN) activity will help to quantitatively connect the chemical characteristics and water uptake properties of WSOM. Copyright © 2020 American Association for Aerosol Research